2016
DOI: 10.1371/journal.pone.0167323
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-Targeted Decyl-Triphenylphosphonium Enhances 2-Deoxy-D-Glucose Mediated Oxidative Stress and Clonogenic Killing of Multiple Myeloma Cells

Abstract: Therapeutic advances have markedly prolonged overall survival in multiple myeloma (MM) but the disease currently remains incurable. In a panel of MM cell lines (MM.1S, OPM-2, H929, and U266), using CD138 immunophenotyping, side population staining, and stem cell-related gene expression, we demonstrate the presence of stem-like tumor cells. Hypoxic culture conditions further increased CD138low stem-like cells with upregulated expression of OCT4 and NANOG. Compared to MM cells, these stem-like cells maintained l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 116 publications
0
9
0
1
Order By: Relevance
“…Our data show that the proteasome inhibitor bortezomib, a widely-used drug in MM, has no effect on AIF1 expression, cleavage and localization; suggesting that PAA could be applied in MM patients, who are resistant to bortezomib. Targeting mitochondria proteins, such as CDDO and 10-TPP, etc., have been shown to enhance the chemotherapeutic effects in pre-clinical and clinical MM studies [ 2 , 34 , 35 ]. Future work will focus on the selection of those promising agents which have specific toxicity to MM cells but spare normal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show that the proteasome inhibitor bortezomib, a widely-used drug in MM, has no effect on AIF1 expression, cleavage and localization; suggesting that PAA could be applied in MM patients, who are resistant to bortezomib. Targeting mitochondria proteins, such as CDDO and 10-TPP, etc., have been shown to enhance the chemotherapeutic effects in pre-clinical and clinical MM studies [ 2 , 34 , 35 ]. Future work will focus on the selection of those promising agents which have specific toxicity to MM cells but spare normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…PAA-induced cell death depends on cellular iron content and cleavage of apoptosis-inducing factor 1 (AIF1), a mitochondrial biogenesis related gene [ 1 ]. Furthermore, increasing intracellular steady-state pro-oxidant levels in stem-like and mature MM cells using a mitochondrial-targeting agent decyl-triphenylphosphonium (10-TPP) promotes cancer cell death [ 2 ]. Though many pre-clinical studies for targeting mitochondria have been reported in MM [ 3 , 4 ], it remains unclear whether mitochondrial biogenesis is beneficial or detrimental for tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ex vivo analysis showed that pharmacological-dosed ascorbic acid (PAA; ultra-high doses of vitamin C) selectively induced apoptosis in primary multiple myeloma cells while not significantly harming other bone marrow cells, and PAA-induced apoptosis in the multiple myeloma cell line OCI-MY5 could be inhibited by NAC (Xia et al, 2017). Furthermore, treatment with a mitochondrial-targeting agent decyltriphenylphosphonium (10-TPP) increased intracellular steady-state pro-oxidant levels and apoptosis in multiple myeloma cell lines (Schibler et al, 2016); 10-TPP is a lipophilic agent that associates directly with mitochondria, likely with the inner membrane (Murphy, 2008;Ross et al, 2008;Schibler et al, 2016). Dexamethasone, a glucocorticoid, is another hydrophobic lipophilic molecule that induced apoptotic cell death in multiple myeloma cell lines, and this effect could also be reduced by NAC (Bera et al, 2010); in sharp contrast, in normal cells dexamethasone was found to inhibit ROS generation (Dandona et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ex vivo analysis showed that pharmacological-dosed ascorbic acid (PAA; ultra-high doses of vitamin C) selectively induced apoptosis in primary multiple myeloma cells while not significantly harming other bone marrow cells, and PAA-induced apoptosis in the multiple myeloma cell line OCI-MY5 could be inhibited by NAC (Xia et al, 2017). Furthermore, treatment with a mitochondrial-targeting agent decyltriphenylphosphonium (10-TPP) increased intracellular steady-state pro-oxidant levels and apoptosis in multiple myeloma cell lines (Schibler et al, 2016); 10-TPP is a lipophilic agent that associates directly with mitochondria, likely with the inner membrane (Murphy, 2008;Ross et al, 2008;Schibler et al, 2016). Dexamethasone, a glucocorticoid, is another hydrophobic lipophilic molecule that induced apoptotic cell death in multiple myeloma cell lines, and this effect could also be reduced by NAC (Bera et al, 2010); in sharp contrast, in normal cells dexamethasone was found to inhibit ROS generation (Dandona et al, 1999).…”
Section: Discussionmentioning
confidence: 99%